Sistem Pemantau Pelanggaran Lalu Lintas Pada Traffic Light Menggunakan Sensor SRF04 Dan Kamera Berbasis Mikrokontroler AtMega8535 - Nugroho, Aji Brahma (Universitas Muhammadiyah Jember, 2019)
Monitoring System Traffic Violations In Traffic Light Uses SRF04 Sensor and Camera, Based Microcontroller ATmega8535 is a tool designed to facilitate the Traffic Police in a curb traffic in the area of Traffic Light. The purpose of making this tool is to minimize accidents that often happen because of many motorists who broke a red light while making the Traffic Police should not continue to maintain the traffic light area. This final report discusses the design and operation of mechanical sensor SRF04, the working principle of this device is when the red light circuit will be active, so when there is a vehicle across the finish line the red light sensor SRF04 which has been positioned on the line will send commands to the microcontroller then microcontroller instruct the camera to take pictures as much as 8 images with a gap of 1 second per 1 picture breach, the response time of the camera to the object get the average duration - mean and standard deviation of 10/19 milliseconds, and the response time of the sensor SRF04 object gets mean duration - average and a standard deviation of 43 milliseconds. The results obtained from this tool manufacture is to produce a tool that can monitor traffic automatically at traffic light.Data SDYhttps://materassomemory.org/https://visualresearchnetwork.org/https://brazoriafumc.org/https://atmamayor.com/https://viralblasts.com/Bloom ScapeRokokbetRokokbetScatter HitamRokokbethttps://press.umam.edu.my/Rokokbethttps://theusajournals.com/RokokbetShiowlaRokokbetRokokbetRokokbetRokokbetRokokbetShiowla